Standard handbook of environmental science, health, and technology (McGraw-Hill, 2000)
The most comprehensive single volume ever assembled for the environmental professional--a one-stop, all-under-one-roof overview of environmental engineering subject areas, and a task-simplifying toolkit designed to simplify day-to-day decisions. Covers the varied topics of interest for today's environmental scientist: mathematical modeling, statistics, plant pathology, as well as engineering problem-solving, management decision-making, and public communication. The perfect resource for biologists, hydrologists, geologists, engineers, chemists, and toxicologists. Packed with numerous tables, charts, illustrations, sampling methods, monitoring methods, testing methods, control techniques, equipment maintenance procedures, and calculation methods. Includes lesson-filled editorial commentary by many of the nearly 100 environmental scientists who have contributed to this book.